Regional Differences in the Level of Inflammation Between the Right and Left Coronary Arteries – a Coronary Computed Tomography Angiography Study of Epicardial Fat Attenuation Index in Four Scenarios of Cardiovascular Emergencies - Blîndu Emanuel; Benedek Imre; Rodean Ioana-Patricia; Halațiu Vasile-Bogdan; Raț Nora; Țolescu Constantin; Mihăilă Theofana; Roșca Aurelian; Mátyás Botond-Barna; Szabó Evelin; Gerculy Renáta; Păsăroiu Dan; et al. (Journal of Cardiovascular Emergencies, 2023)
The pericoronary fat attenuation index (FAI) is an emerging computed tomography-derived marker for measuring vascular inflammation at coronary vessels. It holds prognostic significance for major cardiovascular events and enhances cardiac risk assessment, complementing traditional risk factors and coronary artery calcium scores. However, the impact of local coronary circulation factors on pericoronary inflammation development in right versus left coronary arteries has not been clearly understood.